Primary analysis of malignant neoplasm trends and demographics in hospitalized patients in Kashi prefecture from 2016 to 2023 - Nueraili Kade; Wusiman Yakufu; Cheng Zhang; Lin Wang; Qingqing Qian; Xiaochuan Liu; Long Jia; Chunfeng Wu; Weihua Chen; Tianxiang Chen (BMC Cancer)
Abstract Objective To analyze the ranking, composition, trend changes, and distribution by gender and ethnicity of malignant neoplasms in hospitalized patients in the Kashi prefecture from 2016 to 2023. This analysis aims to provide a reference for the prevention and treatment of malignant neoplasms, screening programs, public education, medical resource allocation, and the development of hospital developments in the Kashi prefecture. Methods We collected the front-page data of medical records for malignant neoplasm patients from 2016 to 2023 at four comprehensive hospitals in the Kashi prefecture, and analyze the ranking, composition, and trend changes of diseases among hospitalized patients with malignant neoplasms. Results A total of 8,386 patients with malignant neoplasms were hospitalized. The number of hospitalizations for patients with malignant neoplasms showed an increasing trend from 2016 to 2023. The incidence of malignant neoplasms began to rise rapidly after the age of 40 and peaks at 70 years old. Among the top 10 types of malignant neoplasms, there were 5,918 hospitalizations, accounting for 70.5% of cases. Of these, gastrointestinal malignancies constituted 43.6%. The most common malignant neoplasm in males was malignant neoplasm of stomach, while in females, it was malignant neoplasm of cervix uteri. Differences in the ranking of malignant neoplasm were observed among different ethnic groups, with malignant neoplasm of gastrointestinal accounting for as high as 44.8% among minority ethnicities. Conclusion The most common malignant neoplasms requiring hospitalization in this area include those of the stomach, esophagus, cervix uteri, breast, and colorectum. Health promotion and early screening strategies should be tailored based on the observed hospitalization patterns. Additionally, medical resources should be allocated efficiently, and support for relevant disciplines should be strengthened to address these prevalent conditions.